A CONSIDERABLE TEACHING METHOD USED IN ENGLISH MORPHOLOGY CLASS: TEAM-BASED LEARNING FOR INDONESIAN LEARNERS - Imamatul Khair (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Morphology is related to English knowledge that provides students with word structure and word formation. The areas of morphology are often problematic for students at English Department because of learning small pieces of words in a language. The objective of this research was to know a suitable learning and teaching method in class of Morphology. 12 samples were taken as respondents that answered several questions related to Morphology learning process in class. They are students at English Department, Universitas Airlangga who currently completed their course on Introduction to English Morphology Class C. It was found that the lecturer in  that class tried to apply team-based learning that is involved in Cooperative Language Learning method. CLL gives students more chances to explore the studied lesson and it gives social impact for those who lack social skills. However, it is likely to sign that every teaching method in class should consider individual learning that students are used to do.